2015
DOI: 10.1016/j.jenvman.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic wastewaters treatment by electrocoagulation to remove silver nanoparticles produced by different routes

Abstract: Nanoscience is a field that has stood out in recent years. The accurate long-term health and environmental risks associated with these emerging materials are unknown. Therefore, this work investigated how to eliminate silver nanoparticles (AgNPs) from synthetic effluents by electrocoagulation (EC) due to the widespread use of this type of nanoparticle (NP) in industry and its potential inhibition power over microorganisms responsible for biological treatment in effluent treatment plants. Synthesized AgNPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In another study, electrocoagulation techniques were used to treat silver nanoparticles from synthetic effluent. Four different chemicals were used, and the results included 98% removal with sodium citrate used as reducing and stabilizing agent, 99.9% removal with sodium borohybride as reducing agent, 99.8% with D-glucose and sodium pyrophosphate as stabilizing agent, and 99.9% removal with sodium pyrophosphate as stabilizing and sodium borohybride as reducing agent [25]. Activated sludge biological flocs were also used successfully to remove silver nanoparticles [26].…”
Section: Comparison Of Synthetic and Natural Coagulant For Silver Nanmentioning
confidence: 99%
“…In another study, electrocoagulation techniques were used to treat silver nanoparticles from synthetic effluent. Four different chemicals were used, and the results included 98% removal with sodium citrate used as reducing and stabilizing agent, 99.9% removal with sodium borohybride as reducing agent, 99.8% with D-glucose and sodium pyrophosphate as stabilizing agent, and 99.9% removal with sodium pyrophosphate as stabilizing and sodium borohybride as reducing agent [25]. Activated sludge biological flocs were also used successfully to remove silver nanoparticles [26].…”
Section: Comparison Of Synthetic and Natural Coagulant For Silver Nanmentioning
confidence: 99%
“…The electric current applied to the treatments was based on the literature, ranging from 0.3 A to 0.9 A (Ghanbari et al, 2014;Matias et al, 2015). For better electron conductivity in the e uent, 1 g L -1 of NaCl was added to each treatment.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…The wires used were of a 6 mm gauge, stripped 10 cm at one end to wrap the slag and 5 cm at the other end to connect to the power source, being changed at each experiment. The electric current applied in the treatments was based on the literature, ranging from 0.3 A to 0.9 A (Ghanbari et al, 2014;Matias et al, 2015). For better electron conductivity in the e uent, 1 g L -1 of NaCl was added to each treatment.…”
Section: Electrochemical Reactormentioning
confidence: 99%
“…Studies have shown that silver nanoparticles can kill liver cells and rat brain cells, in addition to cell death, through the binding of the AgNP to the membrane surface, interfering with cellular respiration and permeability (JU-NAM;LEAD, 2008;BYSTRZEJEWSKA-PIOTROWSKA;GOLIMOWSKI;URBAN, 2009;STANLEY, 2014;ROY et al, 2014;BOUR et al, 2015;DWIVEDI et al, 2015;CANESI;CIACCI;BALBI, 2015;MATIAS et al, 2015). The use of these materials generates nano-residues, which can exhibit various behavior such as agglomeration, aggregation and coating of biomolecules, yet unknown, which regulate the properties of their toxicity (LYNCH; WEISS; VALSAMI-JONES, 2014).…”
Section: Introductionmentioning
confidence: 99%